REPRESENTASI QUARTER LIFE CRISIS DALAM LIRIK LAGU “ZOMBIE” (ENGLISH VERSION) OLEH DAY6: ANALISIS SEMIOTIKA ROLAND BARTHES - Kinanti Christya Wulandari; Nunik Hariyani; Zulin Nurchayati (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
As a cultural product, music is not only a form of entertainment but also a medium for expressing the psychological struggles of young adults. This study aims to analyze how Quarter Life Crisis is represented through the lyrical signs in the song “Zombie” (English Version) by DAY6. Using a descriptive qualitative approach, this research applies Roland Barthes’ semiotic analysis to uncover denotative, connotative, and mythological meanings, supported by Stuart Hall’s theory of representation and Berger and Luckmann’s paradigm of social construction. The primary aim is to analyze how the meaning of Quarter Life Crisis is socially constructed and communicated. The findings reveal that the lyrics represent emotional states commonly associated with Quarter Life Crisis such as emptiness, overthinking, loneliness, and the sense of being trapped. These meanings are embedded in metaphoric expressions like “became a zombie”, “meaningless life”, and “wishin’ to stop and close my eyes.” Through layered meanings, the song deconstructs the modern myths surrounding youth and success. The research concludes that lyrics can serve as a powerful medium for representing the internal crises experienced by young generations and can reflect broader social realities through symbolic language. This study contributes to understanding music as a reflective space for cultural and psychological phenomena among early adulthood generations. Keywords: emptiness, music, quarter life crisis, representation, semiotics